2015
DOI: 10.1016/j.pedn.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Trial of Text-Messaging for Symptom Awareness and Diabetes Knowledge in Adolescents With Type 1 Diabetes

Abstract: Adolescents with type 1 diabetes typically receive clinical care every 3 months. Between visits, diabetes-related issues may not be frequently reflected, learned, and documented by the patients, limiting their self-awareness and knowledge about their condition. We designed a text-messaging system to help resolve this problem. In a pilot, randomized controlled trial with 30 adolescents, we examined the effect of text messages about symptom awareness and diabetes knowledge on glucose control and quality of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…A total of ten RCTs [28–37] and three non-RCTs [3840] measured HbA1c as a clinical indicator of diabetes self-management. Five of the RCTs demonstrated low risk [28, 3335, 37] three RCTs had unknown risk [29, 30, 36], one RCT had moderate risk [32] and one had moderate-high risk of bias [31]. Of the non-RCTs, two demonstrated a moderate risk of bias [38, 40] and one demonstrated a high risk of bias [39].…”
Section: Resultsmentioning
confidence: 99%
“…A total of ten RCTs [28–37] and three non-RCTs [3840] measured HbA1c as a clinical indicator of diabetes self-management. Five of the RCTs demonstrated low risk [28, 3335, 37] three RCTs had unknown risk [29, 30, 36], one RCT had moderate risk [32] and one had moderate-high risk of bias [31]. Of the non-RCTs, two demonstrated a moderate risk of bias [38, 40] and one demonstrated a high risk of bias [39].…”
Section: Resultsmentioning
confidence: 99%
“…The glycemic control is even better if diabetes education is done by a combination of SMS and internet methods, i.e., 86% effect in comparison with 44% that is achieved by SMS alone [93]. Positive results of e-mail and SMS education can also be seen in improved quality of life [94].…”
Section: Educationmentioning
confidence: 99%
“…While mHealth interventions have been efficacious for a variety of indications [ 9 , 10 , 13 ], a downside to these methods may be low levels of engagement. Studies have provided participants with cell phones or prepaid phone cards to facilitate their participation [ 12 , 15 ]. Others have reported that technical problems led to a loss of data and affected the participants’ levels of motivation to continue in the study [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have provided participants with cell phones or prepaid phone cards to facilitate their participation [ 12 , 15 ]. Others have reported that technical problems led to a loss of data and affected the participants’ levels of motivation to continue in the study [ 15 - 18 ]. Past studies have assessed feasibility as participant satisfaction and rates of participant retention [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation